Changes in Candida albicans, Streptococcus mutans and oral health conditions following Prenatal Total Oral Rehabilitation among underserved pregnant women. Issue 8 (August 2021) - Jang, Hoonji; Al Jallad, Nisreen; Wu, Tong Tong; Zeng, Yan; Fadaak, Ahmed; Malmstrom, Hans; Fiscella, Kevin; Xiao, Jin
Abstract: Objectives: To assess the oral health condition and oral microbial outcomes from receiving an innovative treatment regimen - Prenatal Total Oral Rehabilitation (PTOR). Methods: This prospective cohort study included 15 pregnant women in the PTOR group who had a baseline visit before PTOR and three follow-up visits (immediate after, 2 weeks and 2 months) after receiving PTOR. A historical control group of additional 15 pregnant women was matched from a separate study based on a propensity score. Along with demographic and medical background, oral health conditions and perinatal oral health literacy were assessed. Oral samples (saliva and plaque) were analyzed to identify and quantify Streptococcus mutans and Candida species by culturing-dependent and -independent methods. Results: Significant reductions of salivary S. mutans were observed following PTOR, the effect remained until 2-month follow-up ( p < 0.05). The carriage of salivary and plaque S. mutans at the 2-month visit of the PTOR group was significantly lower than that of the control group ( p < 0.05). Oral health conditions reflected by BOP and PI were significantly improved upon receiving PTOR ( p < 0.05). Receiving PTOR significantly improved the perinatal oral health literacy score, and the knowledge retained until 2-month follow-up ( p < 0.05). Conclusions: PTOR is associated with an improvement in oral health conditions and perinatal oral health literacy, and a reduction in S. mutans carriage, within a 2-month follow-up period. Future clinical trials are warranted to comprehensively assess the impact of PTOR on the maternal oral flora other than S. mutans and Candida, birth outcomes, and their offspring's oral health. Abstract : Pregnancy, Prenatal oral health care, Streptococcus mutans, Candida albicans, Total oral rehabilitation, Health benefits